Poisson-Boltzmann Theory of Bionanosystems (Communications in Computational Physics, 2008)
The structure and function of BNS (bionanosystems) such as macromolecules,viruses and ribosomes are strongly affected by electrostatic interactions. Yet theirsupra-million atom size makes them difficult to simulate via a straightforward Poisson-Boltzmann (PB) approach. Here we explore a multiscale approach that results in acoarse-grained PB equation that follows rigorously from the all-atom PB equation. Thederivation of the coarse-grained equation follows from an ansatz on the dependence ofthe electrical potential in two distinct ways, i.e. one reflecting atomic-scale variationsand the other capturing nanometer-scale features. With this ansatz and a series expansion of the potential in a length-scale ratio, the coarse-grained PB equation is obtained.This multiscale methodology and an efficient computational methodology provide away to efficiently simulate BNS electrostatics with atomic-scale resolution for the firsttime, avoiding the need for excessive supercomputer resources. The coarse-grainedPB equation contains a tensorial dielectric constant that mediates the channeling of theelectric field along macromolecules in an aqueous medium. The multiscale approachand novel salinity connections to the PB equation presented here should enhance theaccuracy and wider applicability of PB modeling.